Makna Intensi pada Puisi-Puisi Karya Sutardji Calzoum Bachri - Francisco, Apolo S.; Widyaningrum, Heny Kusuma; Prayoga, Widya Galih (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
The study of literary works teaches humans to understand the meaning of life and increases their vision of wisdom and intelligence. Literary works of poetry need to be analyzed with the aim of examining and showing the purpose, message and impression they convey to poetry lovers or readers. The poems entitled